2010
DOI: 10.1299/jamdsm.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bending Fatigue Strength among Spur Gears Manufactured by Various Methods (Influence of Manufacturing Method on Bending Strength)

Abstract: This paper deals with an experimental evaluation of bending fatigue strengths for hobbed, forged, sintered and austempered ductile iron (ADI) spur gears. The module is 2.5 and the number of teeth is 26 in the test gears. The materials of the test gears are SCr420H for hobbed and forged gears, prealloyed powder metal with 1.5 wt.% Mo for sintered gears, and FCAD 1100-15 for ADI gears. All gears except ADI gears were carburized. The pulsator bending fatigue tests were carried out for the test gears. Then the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…This production would consistently increase if PM technology could provide, in a cost-efficient way, parts having better fatigue performances, comparable to the ones of wrought equivalent parts. With this purpose, many studies have been focused on characterisation of the fatigue behaviour of sintered steels [1–9]. Among different automotive components, gears are the ones that led to a significant cost savings when the wrought alloys are converted to net shape or near-net shape P/M parts.…”
Section: Introductionmentioning
confidence: 99%
“…This production would consistently increase if PM technology could provide, in a cost-efficient way, parts having better fatigue performances, comparable to the ones of wrought equivalent parts. With this purpose, many studies have been focused on characterisation of the fatigue behaviour of sintered steels [1–9]. Among different automotive components, gears are the ones that led to a significant cost savings when the wrought alloys are converted to net shape or near-net shape P/M parts.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars [7,8] observed the microstructure properties of carburized gears to find the initiation and extension of damage; however, this method is only applicable to some specific materials and conditions. Yamanaka et al [9] used four different manufacturing methods for spur gears and found that forging is the best way to increase bending stress of carburized gears. Zwolak and Palczak [10] studied the influence of two treatment methods on contact strength of gears by analysing the characteristic of surface layer, which did not involve bending and shear stresses.…”
Section: State Of the Artmentioning
confidence: 99%
“…This clearly impacts on the stiffness, tensile, fatigue and wear properties of such components [2][3][4]. In the context of P/M gears, (i) the lower stiffness is detrimental to the mesh precision and mesh power loss factor [5], (ii) inferior fatigue properties negatively affect tooth root bending fatigue strength [6] and pitting resistance [7], and (iii) sintered tooth flanks have higher wear rates [8]. To combat these adverse effects, many treatments have been devised so far, such as shot peening [9], surface rolling [10], sinter-forging [11], and the double press double Metals 2019, 9,599; doi:10.3390/met9050599 www.mdpi.com/journal/metals Metals 2019, 9,599 2 of 14 sinter process [12].…”
Section: Introductionmentioning
confidence: 99%